The Epic of the Thalamus in Anatomical Language - García-Cabezas, Miguel Ángel; Pérez-Santos, Isabel; Cavada, Carmen (Frontiers in Neuroanatomy, 2021)
Understanding the origin of Greek and Latin words used as metaphors to label brain structures gives a unique window into how scientific and medical knowledge was produced, preserved, and transmitted through generations. The history of the term thalamus exemplifies the complex historical process that led to the current anatomical terminology. From its first mention by Galen of Pergamon in the 2nd century A.D. to its definitive and current use by Thomas Willis in 1664, the thalamus had an epical journey through 1500 years across Europe, the Middle East, and the North of Africa. The thalamus was confusingly described by Galen, in the Greek language, as a chamber to the brain ventricles. The term thalamus was transferred from Greek to Syriac through the translations of Galen’s books done in Baghdad and also from Syriac to Arabic. Then, it was translated in Europe during the Middle Ages from the Arabic versions of Galen’s books to Latin. Later, during the Early Renaissance, it was translated again to Latin directly from the Greek versions of Galen’s books. Along this epical journey through languages, the term thalamus switched from referring to a hollow structure connected to brain ventricles to naming a solid structure at the rostral end of the brainstem. Finally, the thalamus was translated from Latin to modern languages, where it is used, until today, to name a nuclear complex of subcortical gray matter in the lateral walls of the third ventricle.